HOW CAN THE ELEMENTARY SCIENCE PROGRAM REVEAL, NOURISH, AND MAINTAIN SCIENCE TALENT? - Bingham, N. Eldred (Science Education, 1956)
The article focuses on the controversy on how the elementary science program can reveal, nourish, and maintain science talent. If the elementary science program is to reveal, nourish, and maintain science talent, it must be so organized that those boys and girls who possess aptitudes in science will have an opportunity for the expression and development of these aptitudes. It is important to have researches to see how to provide a situation where boys and girls may live the scientific approach in their classroom activities.